Pengaruh Intensitas Penerangan Terhadap Kelelahan Mata dan Produktivitas pada Pekerja Bagian Operator Jahit CV. Maju Abadi Garment Sukoharjo - Muryadi, Seto; , Tarwaka, PGDip Sc, M.Erg; , Sri Darnoto S.KM M.PH (2015)
CV. Maju Abadi Garment is a textile company which process the textile material become apparel product in which the product will be sold to consumer. The quality and time of production requirement needed needs a high accuracy. The propuse of this research is to know the influence of lightning intensity to the eyestrain and the productivity of sewing operator worker at CV. Maju Abadi Garment Sukoharjo. This research used quasi experiment with non equivalent control group design. The populations of this are 166 workers. The samples are 82 people which decided by proporsional cluster sampling technique. Statistic testing result shows that there is influence of lightining intensity to the eyestrain of sewing operator worker, p-value (0,024<0,05). And the from the productivity statistic testing shows that there is influence of the lightning intensity to the productivity of sewing operator worker, p-value (0,047<0,05). So it can be concluded that there is significant influence between lightning intensity to the eyestrain and the productivity of sewing operator worker at CV. Maju Abadi Garment Sukoharjo.